2017
DOI: 10.3390/nano7030065
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsified D-Limonene Reduces the Heat Resistance of Salmonella Senftenberg over 50 Times

Abstract: Salmonella Senftenberg is a pathogen agent causative of foodborne disease and it is considered the most heat-resistant serovar within this genus. Food industries use heat treatment and chemical antimicrobials in order to eliminate this microorganism in food, but consumers prefer natural antimicrobials as essential oils and their components. This study evaluates the combined effect of thermal treatments and different concentrations of D-limonene nanoemulsion on the inactivation of Salmonella (S.) Senftenberg. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
(55 reference statements)
0
10
0
2
Order By: Relevance
“…For E. coli K12 MG1655 in BHI a value of 0.47 (sd = 0.003) was estimated for c , whereas 1.98 (sd = 0.01) was estimated for E. coli CECT 515 in PW. Previous research works have shown that the microbial response to thermal treatments can vary between strains and/or heating media (Aryani et al, 2015 ; Aspridou and Koutsoumanis, 2015 ; Ros-Chumillas et al, 2017 ). Therefore, it is reasonable to consider that stress acclimation may also be dependent of these factors.…”
Section: Resultsmentioning
confidence: 99%
“…For E. coli K12 MG1655 in BHI a value of 0.47 (sd = 0.003) was estimated for c , whereas 1.98 (sd = 0.01) was estimated for E. coli CECT 515 in PW. Previous research works have shown that the microbial response to thermal treatments can vary between strains and/or heating media (Aryani et al, 2015 ; Aspridou and Koutsoumanis, 2015 ; Ros-Chumillas et al, 2017 ). Therefore, it is reasonable to consider that stress acclimation may also be dependent of these factors.…”
Section: Resultsmentioning
confidence: 99%
“…It provides mathematical models whose applications include the prediction of the microbial response to environmental conditions, such as those encountered during storage or food processing [24]. Another use of predictive models is inference, where the response to different bacteria is compared in order to, for instance, identify the most resistant bacterial strain to some treatment [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the D-value describes the treatment time required to reduce the microbial count a 90% [33]. Model parameters estimated under certain conditions are commonly used to, for example, infer the effectiveness of a treatment [6,34]. Therefore, in many situations, the objective of experiments designed in the context of predictive microbiology is not prediction but the estimation of model parameter with enough precision (standard deviation) that enables accurate inference.…”
Section: Introductionmentioning
confidence: 99%
“…Among the essential oils, D-limonene has shown remarkable antimicrobial properties when combined with thermal treatments 20,[25][26][27] . D-limonene is an important flavour component in citrus essential oil (lemon, orange, tangerine, etc.…”
mentioning
confidence: 99%
“…), and has the generally regarded as safe (GRAS) status 28 . Maté et al 25,26 and Ros-Chumillas et al 27 have studied the synergistic effect of a mild heat treatment and an essential oil nanoemulsion. The synergistic effect led to a 100-fold reduction of the thermal resistance of L. monocytogenes both in culture medium 26 and in apple juice 25 , and a 50-fold reduction of the thermal resistance of Salmonella Senftenberg 27 , which are, by far, the largest reductions in microbial heat resistance ever published when combining heat with natural antimicrobials.…”
mentioning
confidence: 99%